Dual‐Crosslinked Amorphous Polysaccharide Hydrogels Based on Chitosan/Alginate for Wound Healing Applications - Hu, Yang; Zhang, Zhenyan; Li, Yang; Ding, Xiaokang; Li, Dawei; Shen, Chuanan; Xu, Fu‐Jian (Macromolecular rapid communications., 2018)
Development of advanced wound dressing materials with rapid healing rates is in urgent demand for wound cares. A suitable microenvironment will promote cell proliferation and migration, which benefits to early wound healing and prevents inflammations and scars. In this work, N‐carboxymethyl chitosan‐ and alginate‐based hydrogels are prepared via both electrostatic interaction and divalent chelation with epidermal growth factor (EGF) payload to promote the cell proliferation and wound healing. The dual‐crosslinked hydrogels are investigated in terms of rheology, water retention ability, and the release rate of EGF. Moreover, such amorphous hydrogel can promote cell proliferation and accelerate wound healing. The present study demonstrates that dual‐crosslinked polysaccharide hydrogels are promising in wound care management. An N‐carboxymethyl chitosan‐ and alginate‐based dual‐crosslinked amorphous polysaccharide hydrogel with epidermal growth factor payload is prepared through dual electrostatic interaction and divalent chelation. The suitable mechanical properties, good water retention ability and sufficient loading, and release of epidermal growth factor behavior impart the hydrogel with accelerated wound healing efficiency in an animal scald wound model.